Motilin Comparative Study: Structure, Distribution, Receptors, and Gastrointestinal Motility - Kitazawa, Takio; Kaiya, Hiroyuki (Frontiers in Endocrinology, 2021)
Motilin, produced in endocrine cells in the mucosa of the upper intestine, is an important regulator of gastrointestinal (GI) motility and mediates the phase III of interdigestive migrating motor complex (MMC) in the stomach of humans, dogs and house musk shrews through the specific motilin receptor (MLN-R). Motilin-induced MMC contributes to the maintenance of normal GI functions and transmits a hunger signal from the stomach to the brain. Motilin has been identified in various mammals, but the physiological roles of motilin in regulating GI motility in these mammals are well not understood due to inconsistencies between studies conducted on different species using a range of experimental conditions. Motilin orthologs have been identified in non-mammalian vertebrates, and the sequence of avian motilin is relatively close to that of mammals, but reptile, amphibian and fish motilins show distinctive different sequences. The MLN-R has also been identified in mammals and non-mammalian vertebrates, and can be divided into two main groups: mammal/bird/reptile/amphibian clade and fish clade. Almost 50 years have passed since discovery of motilin, here we reviewed the structure, distribution, receptor and the GI motility regulatory function of motilin in vertebrates from fish to mammals.